High-throughput SPR sensor for food safety - Piliarik, Marek; Párová, Lucie; Homola, Jiří (Biosensors & bioelectronics, 2009)
High-throughput surface plasmon resonance (SPR) biosensor for rapid and parallelized detection of nucleic acids identifying specific bacterial pathogens is reported. The biosensor consists of a high-performance SPR imaging sensor with polarization contrast and internal referencing (refractive index resolution 2 x 10(-7) RIU) and an array of DNA probes microspotted on the surface of the SPR sensor. It is demonstrated that short sequences of nucleic acids (20-23 bases) characteristic for bacterial pathogens such as Brucella abortus, Escherichia coli, and Staphylococcus aureus can be detected at 100 pM levels. Detection of specific DNA or RNA sequences can be performed in less than 15 min by the reported SPR sensor.
Keywords: Bacteria, Aerobic; Reproducibility of Results; senzitivita a specificita; kontaminace potravin; analýza selhání vybavení; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; analýza potravin; Food Contamination; Surface Plasmon Resonance; Biosensing Techniques; biosenzitivní techniky; reprodukovatelnost výsledků; povrchová plasmonová rezonance; Financing, Organized; Equipment Failure Analysis; Sensitivity and Specificity; Oligonucleotide Array Sequence Analysis; DNA bakterií; potravinářská mikrobiologie; Food Microbiology; Equipment Design; Food Analysis; financování organizované; design vybavení; DNA, Bacterial; aerobní bakterie